Tracking an Eruptive Prominence Using Multiwavelength and Multiview Observations on 2023 March 7 - Qingmin Zhang; Yudi Ou; Zhenghua Huang; Yongliang Song; Suli Ma (The Astrophysical Journal)
In this paper, we carry out multiwavelength and multiview observations of the prominence eruption, which generated a C2.3 class flare and a coronal mass ejection (CME) on 2023 March 7. For the first time, we apply the revised cone model to three-dimensional reconstruction and tracking of the eruptive prominence for ∼4 hr. The prominence propagates nonradially and makes a detour around the large-scale coronal loops in active region NOAA 13243. The northward deflection angle increases from ∼36° to ∼47° before returning to ∼36° and keeping up. There is no longitudinal deflection throughout the propagation. The angular width of the cone increases from ∼30° and reaches a plateau at ∼37°. The heliocentric distance of the prominence rises from ∼1.1 to ∼10.0 R _☉ , and the prominence experiences continuous acceleration (∼51 m s ^−2 ) over 2 hr, which is probably related to the magnetic reconnection during the C-class flare. The true speed of the CME front is estimated to be ∼829 km s ^−1 , which is ∼1.2 times larger than that of the CME core (prominence). We conclude that both acceleration and deflection of eruptive prominences in their early lives could be reproduced with the revised cone model.